(+)-Panduratin A induces PANC-1 human pancreatic cancer cell death preferentially under nutrient starvation by inhibiting PI3K/Akt/mTOR/autophagy signaling pathway - Sijia Sun; Min Jo Kim; Ashraf M. Omar; Nguyen Duy Phan; Suresh Awale (Elsevier, 2021)
Background: Human pancreatic cancer cells have an extreme tolerance to nutrition starvation, enabling them to survive in the hypovascular tumor microenvironment, a phenomenon also known as "austerity". Discovery of agents that preferentially inhibit cancer cells' tolerance to nutrition starvation is a unique anti-austerity strategy for the discovery of a new generation of anticancer agents. Purpose: To discover potential anti-austerity agents from Boesenbergia pandurata against the PANC-1 human pancreatic cancer cell line exhibiting cytotoxic effects only under the nutrient-deprived conditions with little or no toxicity under normal conditions. Methods: Phytochemical investigation of B. pandurata was carried out, and preferential cytotoxicity activity of all isolated compounds against PANC-1 cells under nutrient-deprived and nutrient-rich conditions was evaluated. The most active compound, (+)-panduratin A (1), was further investigated for its effect on PANC-1 cell morphology, including live imaging, cell migration, and colony formation inhibitory activities. Finally, a mechanistic investigation was carried out to investigate the active compound's cellular targets. Results: Phytochemical investigation led to the isolation of four compounds (1−4). Among these, (+)-panduratin A (1) was identified as the most active constituent, displaying selective cytotoxicity against PANC-1 human pancreatic cancer cell line under the nutrient-deprived conditions, with a PC50 value of 1.6 μM. (+)-Panduratin A (1) was also found to inhibit PANC-1 cell migration and colony formation. Mechanistically, (+)-panduratin A (1) inhibited the PI3K/Akt/mTOR/autophagy signaling pathway. Conclusion: (+)-panduratin A (1) is a promising lead compound for the anticancer drug development based on the anti-austerity strategy.